Evaluation of Traffic Noise Level in Residential Areas Along Jalan Kluang - Case Study in Sri Gading, Batu Pahat, Johor - Ridzuan, Muhammad Aliff Haiqal; Yean Ghing, Tong (Journal of Structural Monitoring and Built Environment, 2023)
Noise, recognized as an adverse factor affecting human health and overall well-being, poses a significant public health concern. This study focuses on evaluating the traffic noise levels in residential areas along Jalan Kluang. Measurements were conducted in four selected residential areas, namely Taman Sri Saga, Taman Cempaka Putih, Kampung Kluang, and Taman Bahagia Baru, during morning (7.30 am - 9.30 am) and evening (4.00 pm - 6.00 pm) peak hours on weekdays. The results indicated that certain locations exceeded the noise limit that set by the Department of Environment (DOE). Kampung Kluang exhibited LAeq values of 71.10 dBA and 71.48 dBA during the morning and evening peak hours, respectively, surpassing the DOE noise limit. Taman Cempaka Putih also recorded noise levels, with LAeq values of 69.40 dBA and 66.46 dBA during the morning and evening peak hours, respectively. In contrast, Taman Sri Saga and Taman Bahagia Baru demonstrated LAeq values still below the DOE limit during both peak hours. Taman Sri Saga recorded LAeq values of 55.63 dBA and 57.78 dBA, while Taman Bahagia Baru recorded LAeq values of 57.58 dBA and 59.65 dBA during the morning and evening peak hours, respectively. Therefore, it is crucial to address the excessive noise levels in the affected residential areas to mitigate the detrimental effects and ensure a healthier living environment for the affected residents in those areas.